Transnational collaboration for sustainability in higher education: Lessons from a systematic review. (1st December 2017) - Caniglia, Guido; Luederitz, Christopher; Groß, Milena; Muhr, Maximilian; John, Beatrice; Withycombe Keeler, Lauren; von Wehrden, Henrik; Laubichler, Manfred; Wiek, Arnim; Lang, Daniel
Abstract: We continue to understand little about how to best design and operate transnational collaborations between universities to advance research and education for sustainability. This article explores general practices in transnational research and teaching that can provide information and inspiration for the sustainability field. The article follows a systematic review protocol and examines 46 articles involving 147 universities engaged in transnational collaborations. First, it presents the main features of these collaborations according to: (a) locations connected; (b) objectives pursued and subjects addressed; (c) implementation. Second, it discusses how reflecting on challenges and strategies encountered in these collaborations can support transnational sustainability research and education. The article concludes highlighting success factors for transnational collaboration, including: combining local and global considerations; making effective use of digital technologies; capitalizing on cultural and national differences; and making the best of available resources.